Beveridge Report (Pictorial charts with explanatory notes) - Beveridge, William Henry Beveridge, Baron, 1879-1963. Social insurance and allied services
1943-01 1943 1940s 14 pages : illustrations PICTORIAL CHARTS SERVICE. 1. January 1943. THE BEVERIDGE PLAN. (Charts Nos. 1 to 6). "The main feature of the Plan for Social Security is a scheme of social insurance against interruption and destruction of earning power and for special expenditure arising at birth, marriage or death. The scheme embodies six fundamental principles: flat rate of subsistence benefit; flat rate of contribution; unification of administrative responsibility; adequacy of benefit; comprehensiveness; and classification....................Based on them and in combination with national assistance and voluntary insurance as subsidiary methods, the aim of the Plan for Social Security is to make want under any circumstances unnecessary." (Beveridge Report, para. 17). Details of the plan will be found on page 5 and following pages, on which are given all figures illustrated in the Charts. ASSUMPTIONS. The plan is drawn up on the basis of three conditions which are assumed as being necessary for its success. "It assumes allowances for dependent children, as part of its background. The plan assumes also establishment of comprehensive health and rehabilitation services and maintenance of employment, that is to say avoidance of mass unemployment, as necessary conditions of success in social insurance." In the industries now subject to unemployment insurance the Beveridge Report assumes that the average rate of unemployment will in future be about 10% as against the 15% on which the finance of the Unemployment Fund is based. Speaking at Manchester Sir William Beveridge referred to five conditions for maintaining employment. "They were:- A national plan for using resources to meet needs, however the plan was executed; fluidity of labour; planning for export as well as for home needs; planning now, not later; determination." (Times. 12.12.42.) The plan is based on various estimates of the cost of living at different ages (see Charts ) at 1938 prices. To these have been added 25%, on the assumption that the cost of living after the war will be 25% higher than in 1938. It is important to note that the figures arrived at are suggested only as a basis for discussion, and would be changed if the cost of living differed materially. PROS AND CONS. Do we want it? In the first place is Social Security in the sense outlined by Sir William Beveridge desirable? Despite the objections on moral grounds which are expressed in certain quarters (e.g. that the plan will destroy the spirit of independence and sap the moral fibre of the nation, etc.) most people will agree with Sir William Beveridge that the elimination of the worst extremes of want and security is indeed indispensable for a civilised society. 126/TG/377/1/1/153